A skin-permeable polymer for non-invasive transdermal insulin delivery - Qiuyu Wei; Zhi He; Zifan Li; Zhuxian Zhou; Ying Piao; Jianxiang Huang; Yu Geng; Runnan Zhang; Yaqi Fu; Jiayi Ye; Yue Yuan; Haoru Zhu; et al. (Nature, 2025)
Abstract Non-invasive skin permeation is widely used for convenient transdermal delivery of small-molecule therapeutics (less than 500 Da) with appropriate hydrophobicities 1 . However, it has long been deemed infeasible for large molecules—particularly polymers, proteins and peptides 2,3 —due to the formidable barrier posed by the skin structure. Here we show that the fast skin-permeable polyzwitterion poly[2-( N -oxide- N,N -dimethylamino)ethyl methacrylate] (OP) can efficiently penetrate the stratum corneum, viable epidermis and dermis into circulation. OP is protonated to be cationic and is therefore enriched in the acidic sebum and paracellular stratum corneum lipids containing fatty acids, and subsequently diffuses through the intercorneocyte lipid lamella. Beneath the stratum corneum, at the normal physiological pH, OP becomes a neutral polyzwitterion, ‘hopping’ on cell membranes, enabling its efficient migration through the epidermis and dermis and ultimately entering dermal lymphatic vessels and systemic circulation. As a result, OP-conjugated insulin efficiently permeates through the skin into the blood circulation; transdermal administration of OP-conjugated insulin at a dose of 116 U kg −1 into mice with type 1 diabetes quickly lowers their blood glucose levels to the normal range, and a transdermal dose of 29 U kg −1 normalizes the blood glucose levels of diabetic minipigs. Thus, the skin-permeable polymer may enable non-invasive transdermal delivery of insulin, relieving patients with diabetes from subcutaneous injections and potentially facilitating patient-friendly use of other protein- and peptide-based therapeutics through transdermal delivery.